Sociology graduate school requirements and competitive advantages - Duffy, Meghan; Symbaluk, Diane (My University, 2019)
This study examines the admission requirements of Canadian Master of Arts in Sociology programs. A content analysis was performed on a sample of 58 programs based on information provided on department and university websites. Admission requirements centred on high grade point averages, strong letters of support and prior academic and research experience as indicated in a Curriculum Vitae, samples of work or a statement of intent. Results revealed admission preferences for applicants with minimum entrance grades of 80%, an honours degree, prior courses in research methods, statistics and social theory, and a demonstrated research focus. In addition to maintaining high grades, our findings suggest that undergraduates planning to pursue a Master’s degree in sociology should aim to incorporate substantive courses early on in their programs of study and take advantage of other opportunities to develop research skills, networks and training.